2018
DOI: 10.1001/jamaophthalmol.2018.3160
|View full text |Cite
|
Sign up to set email alerts
|

Serial Combined Wide-Field Optical Coherence Tomography Maps for Detection of Early Glaucomatous Structural Progression

Abstract: IMPORTANCE Both parapapillary and macular areas are important in determining the progression of early glaucoma. However, no attempt has been made to assess the progression of glaucoma in images that combine the 2 areas. OBJECTIVE To evaluate the potential usefulness of serial analysis of combined wide-field optical coherence tomography (OCT) maps for detection of structural progression in patients with early glaucoma. DESIGN, SETTING, AND PARTICIPANTS Retrospective observational study. Patients with early prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Our group has reported the advantages of the wide-field RNFL thickness map and also reported the advantage of the wide-field SuperPixel map (DRI-OCT), 12 , 13 or PanoMap (Cirrus OCT). 8 However, these two deviation maps used the normative database of narrow areas based on a uniform size and angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has reported the advantages of the wide-field RNFL thickness map and also reported the advantage of the wide-field SuperPixel map (DRI-OCT), 12 , 13 or PanoMap (Cirrus OCT). 8 However, these two deviation maps used the normative database of narrow areas based on a uniform size and angle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical observation of the retinal nerve fiber layer (RNFL) around the optic disc head (peripapillary), the macular inner retinal structure has received attention in the field of glaucoma. 5 7 Recently, studies on the temporal sequences and spatial relations between the peripapillary and macular areas 8 11 have been published. Some studies have suggested that it may be useful to diagnose glaucoma to integrate these two areas using advanced hardware (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This one-page report was shown to be very helpful in discriminating healthy and glaucomatous eyes when used by a non-glaucoma specialist [59]. Furthermore, SS-OCT single widefield scan was able to distinguish between pre-perimetric and early perimetric glaucoma patients from healthy controls and to detect progression successfully [60][61][62]. Albeit some OCT parameters have been shown to detect glaucoma better than others, it is recommended to consider a combination of parameters in the diagnostic process.…”
Section: Glaucoma Diagnosismentioning
confidence: 84%
“…[10][11][12][13][14] Some reports introduced that integrating these two areas together using hardware (wide-field scan with swept source technology) or software (scan individually and combine each area together) is useful for diagnosing glaucoma or its progression and can provide more complementary information than using each separately. 11,12,[15][16][17][18][19] Our group reported that a serial analysis of PanoMaps, which integrates the deviation map of the peripapillary and macular areas, performed well in detecting structural progression in early glaucomatous eyes. 18 Furthermore, our group introduced a combination method, which integrates the peripapillary RNFL and macular GCIPL Guided Progression Analysis (GPA) progression maps, which were derived from glaucoma progression evaluation software (Cirrus HD-OCT GPA software 2,20 ), into a single image and helps to evaluate the temporal sequence of the glaucomatous structural progression.…”
mentioning
confidence: 99%
“…11,12,[15][16][17][18][19] Our group reported that a serial analysis of PanoMaps, which integrates the deviation map of the peripapillary and macular areas, performed well in detecting structural progression in early glaucomatous eyes. 18 Furthermore, our group introduced a combination method, which integrates the peripapillary RNFL and macular GCIPL Guided Progression Analysis (GPA) progression maps, which were derived from glaucoma progression evaluation software (Cirrus HD-OCT GPA software 2,20 ), into a single image and helps to evaluate the temporal sequence of the glaucomatous structural progression. 17 However, no studies using a combined wide-field GPA map (GPA PanoMap) to determine spatial characteristics and patterns of glaucomatous structural progression have been reported to date.…”
mentioning
confidence: 99%